Production of secondary metabolites using tissue culture-based biotechnological applications - Ozyigit, Ibrahim Ilker; Dogan, Ilhan; Hocaoglu-Ozyigit, Asli; Yalcin, Bestenur; Erdogan, Aysegul; Yalcin, Ibrahim Ertugrul; Cabi, Evren; Kaya, Yilmaz (Frontiers in Plant Science, 2023)
Plants are known to have secondary metabolite reservoirs. Secondary metabolites are present in plant organs including leaf, stem, root, and flower. Although they provide advantages to the plants in many cases, they are not necessary for metabolisms related to growth, development, and reproduction. They are specific to plant species and are precursor substances of them which can be modified for generations of different compounds in different plant species. Secondary metabolites are used in many different industries including in dye, food proceessing and cosmetic industries, in agricultural control, as well as being used as pharmaceutical raw materials by humans in general. For this reason, they are needed to be obtained in abundance using modern technological methods in addition to production with classical methods. Biotechnology uses living organisms, or their derivates to develop useful products for human benefit through direct and indirect applications. One of the most important applications of biotechnology is the production of genetically modified plants, as well as the commercialization of genetically enhanced products that have been adapted for targeted purposes. Secondary metabolites can be obtained by different methods in plant biotechnology. The most important of these methods are tissue culture and gene transfer. Transgenic plants are genetically modified organisms that, in addition to being more productive agriculturally and more commercially effective, are invaluable tools especially for medical purposes and are the source of many secondary metabolites of therapeutic importance. This manipulation so called “creating transgenic plants”, which can also be defined as manipulating the genetic information of a plant by using the genetic material of a different organism and using certain vectors for the transfer of the new genetic code created, can be performed using these two main methods. Currently, many studies are going on this subject, and some of those receiving attention are found to be taken place in plant biotechnology and have promising applications. In this work, in particular of the importance, and benefits of secondary metabolites, and their productions through tissue culture-based biotechnological applications are discussed using literature with presence of current studies.